Characterisation, analysis and optical properties of nanostructure ZnO using the sol-gel method - Muhammad, Kashif; Yarub, Al-Douri, Assoc. Prof. Dr.; Uda, Hashim, Prof. Dr.; Md. Eaqub, Ali; Syed Muhammad Usman, Ali; Willander, Magnus, Prof (Institution of Engineering and Technology (IET), 2013)
Link to publisher's homepage at http://www.theiet.org/